The Commercialization of Islamophobia: Capitalizing on Apprehension - Nasrullah, Riki; Prayogi, Arditya; Lukman, Fahmy; Parmin, Parmin (Perhimpunan Intelektual Muslim Indonesia, 2024)
Islamophobia, the irrational fear, prejudice, or hatred towards Islam and Muslims, has become a pervasive issue in contemporary society. While historical roots of Islamophobia exist, its commercialization has emerged as a distinct phenomenon in recent years. This article explores the commercialization of Islamophobia and its implications, shedding light on how various actors capitalize on apprehension to further their interests. The study employs a literature review approach to analyze and understand the phenomenon, revealing how media, politics, and business exploit and profit from fear, stereotypes, and negative perceptions surrounding Islam and Muslims. The consequences of the commercialization of Islamophobia are profound, perpetuating discrimination, marginalization, and violence against Muslim communities. To counter Islamophobia effectively, collective efforts must be made to dismantle fear-inducing narratives, promote empathy, and foster a comprehensive understanding of Islam and Muslims.